"TECNO RECYCLING" Technology and recycling two tools fused to learn english and computer - Sierra Martínez, Ana Maria; Guzmán Espitia, Diana Marcela; Velásquez Camacho, Leida Yamile (Universidad Francisco de Paula Santander, 2016)
The present research project reveals the causes that generate the absence of the teaching of English and technology and informatics in the students of some Educational Institutions of the rural sector of  Pacho Cundinamarca, this idea of investigation was born when recognizing the influence of These two aspects nowadays and the little interest that has been given here. To know the situation presented previously gives way to the creation and development of an innovative proposal for teaching these two areas through the implementation of pedagogical strategies that enable the student to interact directly with the English and computing, thus creating a significant learning experience. Thinking about making this a quality investigative work, we opted It has been chosen for the quantitative approach and the participatory action research that was applied to the second and third grade students of the I.E.D Aquileo Parra rural headquarter “La Cabrera”; As partial results it has been shown that the students have become aware that these two areas like the others are important in the student's development and should not be neither the context nor the resources impediment to learn them.